Religion and Tradition in Modern Turkey as Reflected in Orhan Pamuk’s Snow Novel: An Analysis of Social Deixis - Annisa Nur Karimah; Jarot Wahyudi (Sunan Kalijaga: International Journal of Islamic Civilization, 2022)
The current study is dedicated to analyse the types of social deixis in Orhan Pamuk’s Snow Novel.Snow is a novel translated from the original Turkish-language novel entitled Kar. The reseacher is interested in the novel because it is telling about the clash of traditions, religion and modernization happening in Turkey In analysing the object of the study, the researcher  applied deixis theory introduced by C.J. Fillmore which concerned with social types of deixis. This study uses a qualitative descriptive method, which describes the phenomena that occur in the novel through the language spoken by the participants based on the context. The researcher undertook three steps in collecting the data, (1)reading the whole chapters of the Snow novel thoroughly to find the data that spread out within the novel and also to fully understand the context of the story, (2)making a list of the deictic expressions that spread out throughout the novel, (3)the researcher collected the data into the table and classified the data based on the social deixis type. As a result, the researcher found 40 forms of deictic expression within five types of social deixis. The data that have been collected from the source of data will be analyzed in several stages as follows, (1)analyzing the deictic expressions in Snow  novel, (2)classifying the data based on each kind of social deixis, (3)explaining the meaning of each kind of social deixis, (4)concluding. Out of five, only one type of social deixis used frquently by the author, i.e., ‘polite’. This is due to most of the participants do not have close relationship with each other.